Analysis of Online Marketing and Online Administration on Consumer Purchase Interests on Shopee Users - Hasanah, Uswatun; Pasaribu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of online marketing and online administration on consumer buying interest on the Shopee e-commerce platform. The method used in this research is to use a qualitative approach by collecting in-depth data regarding online marketing and administration for Shopee users to understand in depth the dynamics of online marketing and administration on the Shopee e-commerce platform. The research results show that effective online marketing, such a data-based advertising, promotions via social media, and influencer strategies, have a significant influence on consumer purchasing interest. Apart from that, good online administration, such as ease in the payment process, delivery and costumer service, also plays an important role in increasing consumer satisfaction and buying interest.